The opposite association of HRAS and KRAS mutations with clinical variables of bladder cancer - M. P. Smal; A. I. Rolevich; T. N. Nabebina; S. A. Krasny; R. I. Goncharova (Вавиловский журнал генетики и селекции)
HRAS, KRAS and NRAS gene products belong to the superfamily of small GTPases. These proteins regulate cellular response to extracellular stimuli by means of activation of different signaling pathways. Although the role of RAS gene mutations in the pathogenesis of various human cancers has been established, the clinical significance of these molecular alterations in bladder cancer remains unclear. The aim of this study was to determine the frequency and spectrum of HRAS, KRAS and NRAS mutations, to analyze their relationships with clinicopathological variables and to determine the prognostic value of these alterations in terms of recurrence, progression and mortality, in a prospective cohort of 249 bladder cancer patients. The frequency of RAS mutations detected by the SNaPshot method, was found to be 11.2 %, of which HRAS mutations accounted for 64.3 %, KRAS, for 28.6 % and NRAS, for 7.1 %. We failed to find any correlation between all RAS mutations and pathomorphological characteristics. However, when analyzed separately, HRAS and KRAS mutations were for the first time shown to be associated with the opposite clinical parameters of bladder cancer: HRAS mutations were significantly associated with low-stage low-grade papillary tumors of a small size (р < 0.05), whereas KRAS mutations were associated with non-papillary urothelial carcinomas and the presence of metastasis (р < 0.05). Analysis of the prognostic value of molecular alterations revealed an association of KRAS mutations with decreased cancer-specific survival in both the whole group of patients and the subgroup with non-muscle invasive disease. The data obtained suggest that HRAS and KRAS gene mutations may characterize alternative pathways of bladder cancer pathogenesis: HRAS mutations indicating benign and KRAS mutations, aggressive disease course.